Textual fundamentals in earnings press releases. (June 2022) - Li, Ken
Abstract: I re-examine the information content of earnings press releases (EPRs) by distinguishing textual fundamentals (TF), which captures information content in non-tone language, from tone, which captures optimism and pessimism and is the focus of prior research. I find after controlling for standard firm characteristics, TF positively predicts future operating performance, unlike tone, which negatively predicts future operating performance. I document a return continuation in TF, in contrast to the return reversal in tone documented in prior literature. My findings distinguish informative content in TF and misleading content in tone in EPRs.